Structure characteristics, solution properties and morphology of oxidized yeast β-glucans derived from controlled TEMPO-mediated oxidation. (15th December 2020) - Ma, Huiyu; Huang, Qilin; Ren, Jiayi; Zheng, Zhaomin; Xiao, Yidong
Highlights: Yeast β-glucan was oxidized by TEMPO from –CH2 OH units into–COO − /–COOH. Solubility, particle size and molecular weight dropped as oxidation degree rose. Four oxidized yeast β-glucan (10.0∼47.3%) had aggregate morphology with different sizes. Oxidized yeast β-glucan (71.2%) showed extended chains, even with a loose network. Adjusting oxidation degree can alter yeast β-glucan's solution properties and morphology. Abstract: This work was to investigate the effect of the degree of oxidation (DO) on the structure, solution properties and morphology of yeast β-glucan. Five different degrees of oxidized yeast β-glucan (OYG1-5) samples were controllably prepared by TEMPO-mediated oxidation on C-6 position. Namely, the –CH2 OH units were oxidized into –COO – /–COOH, and the DO was quantified to be 10.0∼71.2% by potentiometric titration. With an increase of the DO, the OYG samples had a remarkable increase in solubility as indicated by the decreasing turbidity, particle size and zeta-potential, and showed an overall decrease from 2.63 × 10 6 to 1.43 × 10 5 g/mol in molecular weight and from 3.95 to 1.66 in polydispersity. OYG1-4 with DO from 10.0% to 47.3% had aggregate morphology with different sizes, while OYG5 with DO of 71.2% showed uniformly dispersed chains and a loose network formed by chain entanglement. These findings demonstrated that the solution properties and morphology of yeast β-glucan can be altered by adjusting the DO.